Supply Chain Risk Mitigation Using House of Risk in Wood Pellet Manufacturing : Mitigasi Risiko Rantai Pasokan Menggunakan Model House of Risk dalam Industri Pembuatan Pelet Kayu - Nugroho, Aldi Pramoedya; Ernawati, Dira; Dewi, Sinta (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Manufacturing supply chains are vulnerable to operational disruptions caused by uncertainty, making supply chain risk management increasingly important for maintaining operational continuity and competitiveness. Specific Background: PT Komi Biomass Indonesia, a wood pellet manufacturer in the renewable energy sector, experiences supply chain challenges related to raw material shortages, inconsistent wood waste quality, limited skilled labor, machine downtime, and delivery delays. Knowledge Gap: Previous Supply Chain Risk Management studies have largely focused on established companies, while risk mitigation analysis in newly established wood pellet manufacturing companies remains limited, particularly in industries dependent on furniture wood waste supply and renewable energy market dynamics. Aims: This study aims to identify supply chain risk events, determine priority risk agents, and formulate mitigation strategies using the Supply Chain Operations Reference framework and the House of Risk method. Results: The analysis identified 25 risk events and 28 risk agents across the plan, source, make, deliver, and return processes. Pareto analysis determined 14 priority risk agents contributing to 80% of cumulative Aggregate Risk Potential values. Furthermore, 15 preventive mitigation strategies were formulated, with supplier reconfirmation before delivery schedules, periodic supplier quality feedback, and internal maintenance team formation ranked as the highest priorities based on the Effectiveness-to-Difficulty Ratio. Novelty: This study provides a structured supply chain risk mitigation analysis for the emerging wood pellet industry, emphasizing risks associated with biomass raw material dependency and renewable energy transition dynamics. Implications: The findings provide practical guidance for renewable energy manufacturing companies in developing systematic and proactive supply chain risk mitigation strategies to improve operational reliability and supply chain resilience. Highlights: Twenty-five supply chain disruptions and twenty-eight causal factors were identified across SCOR activities. Fourteen dominant causal sources accounted for 80% of cumulative Aggregate Risk Potential values. Supplier coordination, equipment maintenance, and workforce supervision became the main preventive priorities. Keywords: House of Risk, Risk Mitigation, Wood Pellet